Experiences with global trigger tool reviews in five Danish hospitals: an implementation study. Issue 5 (12th October 2012) - von Plessen, Christian; Kodal, Anne Marie; Anhøj, Jacob
Abstract : Objectives: To describe experiences with the implementation of global trigger tool (GTT) reviews in five Danish hospitals and to suggest ways to improve the performance of GTT review teams. Design: Retrospective observational study. Setting: The measurement and monitoring of harms are crucial to campaigns to improve the safety of patients. Increasingly, teams use the GTT to review patient records and measure harms in English and non-English-speaking countries. Meanwhile, it is not clear as to how the method performs in such diverse settings. Participants: Review teams from five Danish pilot hospitals of the national Danish Safer Hospital Programme. Primary and secondary outcome measures: We collected harm rates, background and anecdotal information and reported patient safety incidents (PSIs) from five pilot hospitals currently participating in the Danish Safer Hospital Programme. Experienced reviewers categorised harms by type. We plotted harm rates as run-charts and applied rules for the detection of patterns of non-random variation. Results: The hospitals differed in size but had similar patient populations and activity. PSIs varied between 3 and 12 per 1000 patient-days. The average harm rate for all hospitals was 60 per 1000 patient-days ranging from 34 to 84. The percentage of harmed patients was 25 and ranged from 18 to 33. Overall, 96% of harms were temporary. Infections, pressure ulcers procedure-related and gastrointestinal problems were common. Teams reported differences in training and review procedures such as the role of the secondary reviewer. Conclusions: We found substantial variation in harm rates. Differences in training, review procedures and documentation in patient records probably contributed to these variations. Training reviewers as teams, specifying the roles of the different reviewers, training records and a database for findings of reviews may improve the application of the GTT.